Habsburg Hunting Palace in Vistula – An Attempt at Architectural Reconstruction - ROSŁON-MAZGAJ Katarzyna; SOKÓŁ Małgorzata (Architecture, Civil Engineering, Environment)
The Castle of the President of the Republic of Poland in Vistula is a specific architectural continuation of the Habsburg hunting mansions built in this location. Previously, there was a larch Hunter’s Castle in this place, the residence of the Cieszyn princes from the Habsburg dynasty. It was erected in 1907. In 1927 it was allocated to the seat of the President of the Republic of Poland, but a few days before handing over to the Head of State, a fire destroyed the residence (December 1927). Few photos and plans have survived to our times. Therefore, this residence is an architectural mystery. We do not know its exact plans or room layout. Therefore, the authors have attempted to recreate the architectural formula and function of this Habsburg residence. This task was all the more difficult, as even the oral accounts of this residence are fragmentary. In their work, the authors relied, among other things, on their knowledge of the log structure in which the residence was erected, and on the documentation made available from the collections of the Museum of Cieszyn Silesia. In the study, the authors also referred to the use of computer techniques to assist in the process of developing the present attempt to reconstruct the Castle. These techniques allow a much deeper analysis of the factual material, which is an important source of this study.